PENGARUH STORE ATMOSPHERE, KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA MINISO DI KOTA SAMARINDA - Nur Kumala Danta; Lailatul Hijrah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Along with the rapid progress of information technology, it cannot be denied that it has an impact on the development of the global business world. This business development is marked by the emergence of various types of retail businesses which are currently popular in several countries, so this has resulted in the level of competition in the retail business becoming very competitive, in accordance with the Theory of Reasoned Action (TRA) which explains the relationship between attitudes and behavior, and is a grand theory in this research. The aim of this research is to partially analyze the influence of store atmosphere, product quality and service quality on purchasing decisions. The research method used is a quantitative method with an associative approach using a likert scale. The sampling technique applied was nonprobability sampling with a purposive sampling method, involving 100 respondents from Miniso consumers in Samarinda City. Hypothesis testing was carried out using Statistical Product and Service Solutions Software or SPSS Version 27. The research results showed that the store atmosphere, product quality and service quality variables had a significant effect on purchasing decisions. Thus, the results of this research show that Miniso consumers in Samarinda City really pay attention to the atmosphere of the shop, consider the quality of the products offered, and evaluate the quality of the service provided, so that these things influence their decision to buy at Miniso Samarinda City.